2009
DOI: 10.1534/genetics.108.090829
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Population Genetics of theSRKandSCRSelf-Incompatibility Genes in the Wild Plant SpeciesBrassica cretica(Brassicaceae)

Abstract: Self-incompatibility (SI) in plants is a classic example of a trait evolving under strong frequency-dependent selection. As a consequence, population genetic theory predicts that the S locus, which controls SI, should maintain numerous alleles, display a high level of nucleotide diversity, and, in structured populations, show a lower level of among-population differentiation compared to neutral loci. Population-level investigations of DNA sequence variation at the S locus have recently been carried out in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Indeed, in the class II SCR tree, the clustering of interspecific triplets consisting of one haplotype from each of B. oleracea and B. rapa, together with one putatively functional B. cretica haplotype, is particularly evident (Figure 3). In fact, the entire reservoir of class II haplotypes in cultivated B. oleracea can be found within a single B. cretica population (Edh et al 2009) and, thus, we apparently have not found any functional class II haplotypes not previously known from Brassica in the wild B. cretica. Several closely related pairs of B. cretica/B.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Indeed, in the class II SCR tree, the clustering of interspecific triplets consisting of one haplotype from each of B. oleracea and B. rapa, together with one putatively functional B. cretica haplotype, is particularly evident (Figure 3). In fact, the entire reservoir of class II haplotypes in cultivated B. oleracea can be found within a single B. cretica population (Edh et al 2009) and, thus, we apparently have not found any functional class II haplotypes not previously known from Brassica in the wild B. cretica. Several closely related pairs of B. cretica/B.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, SRK lineages from the cultivated B. oleracea and B. rapa are widely dispersed among lineages from the wild B. cretica. Together with the observation of almost equal levels of SRK sequence polymorphism in wild and cultivated Brassica species (Edh et al 2009), this suggests that domestication has not entailed any severe bottleneck, with subsequent reduction in the number and diversity of lineages, at the Brassica S locus (cf. Igic et al 2004).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations